DEVELOPMENT OF PARTIALLY HYDROLYSED AND DEODOURISED FISH FLOUR. - SETTY, T. M RUDRA; SUDHAKARA, N S; NAGARAJ, A S; CHETTY, H P (Fishery Technology, 2017)
A process developed for preparation of partially hydrolysed and deodouriscd (PHD) fish flour, without solvent extraction is described. The PHD fish flour prepared from four varieties of trash fish, had creamy white colour and contained 87-92% protein and 7-8% available lysine. The products had shelf life of more than an year at room temperature, and caused no grittiness when incorporated in snacks and bakery products at 10% and 7.5% level respectively. The flour prepared from Nemipterus spp. had a PER 2.32 compared to 2.68 of raw fish meat and 2.5 of standard casein.